WANITA DAN KEADILAN: MENAKAR KEADILAN POLIGAMI DALAM NOVEL ATHIRAH - Santi Puspitasari; Qurrotal Ainiyah (State of Islamic Institute Langsa, 2019)
this paper will be explained about how family justice the polygamy based on the gender perspective, which has interpreted through the Athirahh novel. Considering that in this novel tells about the conflict in the polygamous family life carried out by Haji Kalla. Therefore the contributions of this research are: Firstly, the gender justice concept: marriage commitment and relation. The impartiality for a polygamous family is quiet difficult because of the balance of a polygamous family it is not only about the living sharing but also the feeling sharing. There might be a polygamy justice if the couple has a commitment to remain for the couple and maintain the marriage even though there are those who getting hurt because of that polygamy. Secondly, as told in the Athirahh novel, the figure of the woman who was hurt because of the polygamy had been done by her husband, but she was able to manage her mental and keep her good behavior in front of her husband and her children, so that was why the marriage commitment was maintained. But there was an inequality in the relation and the task division because Haji Kalla spent his time with his new wife more than the old one. Athirah had to has burden more because of it. In addition to keep her family, she also had to work for them.